2008
DOI: 10.1007/s10565-008-9065-y
|View full text |Cite
|
Sign up to set email alerts
|

New implications in the use of imposex as a suitable tool for tributyltin contamination: experimental induction in Hexaplex trunculus (Gastropoda, Muricidae) with different stressors

Abstract: Imposex, i.e. the development of additional male sex organs (penis and/or vas deferens), in females of gonochorist marine and freshwater gastropods, is known to be caused by tributyltin (TBT), and it has been widely used as a biomonitoring tool in environmental surveys for TBT pollution assessment. In this study, we experimentally tested the potential to induce imposex by another endocrine disruptor (polychlorinated biphenyls [PCBs] mixture--Aroclor 1260). Adults of Hexaplex trunculus with low imposex level, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
2
12
0
1
Order By: Relevance
“…Concerning the RPSI, the highest degree of imposex found in the present study (RPSI ¼ 18.2%) was lower than that reported for the same species along the Italian Coast by Terlizzi et al 25 In males, it seems that TBT pollution may also impact secondary sexual organs. This observation suggests that factors other than TBT could be implicated on the development of imposex and thus agrees with recent findings reported by Garaventa et al 6 In fact, these authors have experimentally developed imposex in H. trunculus with stressors other than TBT, such as polychlorinated biphenyls (PCBs) and aroclor. However, significant correlations were only obtained for 2007 samples (r ¼ 0.6, p ¼ 0.2 in 2004 and r ¼ 0.8, p ¼ 0.04 in 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Concerning the RPSI, the highest degree of imposex found in the present study (RPSI ¼ 18.2%) was lower than that reported for the same species along the Italian Coast by Terlizzi et al 25 In males, it seems that TBT pollution may also impact secondary sexual organs. This observation suggests that factors other than TBT could be implicated on the development of imposex and thus agrees with recent findings reported by Garaventa et al 6 In fact, these authors have experimentally developed imposex in H. trunculus with stressors other than TBT, such as polychlorinated biphenyls (PCBs) and aroclor. However, significant correlations were only obtained for 2007 samples (r ¼ 0.6, p ¼ 0.2 in 2004 and r ¼ 0.8, p ¼ 0.04 in 2007).…”
Section: Discussionsupporting
confidence: 92%
“…However, significant correlations were only obtained for 2007 samples (r ¼ 0.6, p ¼ 0.2 in 2004 and r ¼ 0.8, p ¼ 0.04 in 2007). In fact, Garaventa et al 6 have studied a population already showing low levels of imposex, and consequently we ignore it if the contaminants used are able to induce imposex. In females, the relationship between TBT concentration and the incidence/degree of imposex was opposite in the stations of Sfax and Gab es fishing harbours, namely in 2004 samples.…”
Section: Discussionmentioning
confidence: 99%
“…immersion in a solution of magnesium chloride until full relaxation), following the protocol proposed for N. lapillus by Gibbs (1999). Anaesthetisation with MgCl 2 has been successfully applied in several gastropod species (mainly for imposex studies), including other muricids such as Dicathais orbita (Noble et al, 2009), H. trunculus (Terlizzi et al, 2004;Vasconcelos et al, 2006;Garaventa et al, 2008), O. erinacea Huet et al, 1995;Gibbs, 1996), Stramonita haemastoma (Rilov et al, 2000) and specifically also in B. brandaris (Ramón & Amor, 2001Chiavarini et al, 2003;Gómez-Ariza et al, 2006). It is widely recognised that anaesthetisation causes the relaxation of the penial muscle, straightening the penis and increasing penis measurement.…”
Section: Discussionmentioning
confidence: 99%
“…trunculus is also considered an excellent bioindicator species of organotin pollution (TBT, tributyltin biocide used in antifouling paints), inducing the development of the sexual abnormality known as imposex (superimposition of penis and vas deferens onto females), which was described in several populations of this species throughout the Mediterranean (e.g., Martoja and Bouquegneau 1988;Axiak et al 1995;Terlizzi et al 1998;Lahbib et al 2009). Some studies reported the possible involvement of contaminants other than tributyltin in the development of imposex, such as copper, nonylphenol, polychlorinated biphenyls (PCBs), aroclor, and metals (Nias et al 1993;Evans et al 2000;Garaventa et al 2008;Lahbib et al 2009). Still, a recent study by Lahbib et al (2013) reported no evidence of relationships between Cu, Zn, and Cd contamination and imposex development in H. trunculus from the Tunisian coast.…”
Section: Introductionmentioning
confidence: 99%